Disablist bullying: An investigation of student teachers? knowledge and confidence. A Report for the Standing Conference on Teacher Education North and South (SCoTENS). - Mc Guckin, Conor (My University, 2011)
This study set out to explore the knowledge and confidence of student teachers in relation to disablist bullying. Two centres for Initial Teacher Education, one in each jurisdiction, were selected for recruitment of participants. Stranmillis University College provided the sample of both primary and post-primary student teachers from Northern Ireland. The School of Education at Trinity College, Dublin and the University's three Associated Colleges of Education (Marino Institute of Education, Froebel College of Education, and the Church of Ireland College of Education) provided the sample for the Republic of Ireland. Adopting a mixed methods approach of four focus groups and a paper questionnaire (n = 257), data were collected and analysed relating first to students' knowledge and confidence in the discrete areas of special educational needs and bullying, and then in relation to disablist bullying. The study highlights the high importance attributed to SEN and bullying by student teachers but also the sporadic provision and low confidence in meeting the needs of children with SEN. The study also reveals that none of the participants in either jurisdiction have received any guidance at all in relation to disablist bullying as part of their Initial Teacher Education. The study concludes with recommendations to address this shortcoming, including the urgent need for practical, solution-focused and evidence-based courses at ITE and CPD level in both jurisdictions. Keywords:
PUBLISHED
A report for the standing conference on teacher education north and south (SCOTENS)
Armagh, Northern Ireland: The Centre for Cross Border Studies.
Keywords: disablist; teachers; SEN; bullying; special educational needs; Inclusive Society